KADAR FERITIN PASIEN COVID-19 - Dewi Astuti; Fuas Sitisari; Dewi Yunita; Eva Ayu Maharani (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Bacground: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2). COVID-19 causes death both in the world and in Indonesia. Ferritin is an iron storage protein, whose levels can increase during viral infection and can be a marker of viral replication.Methdes: The study design used was a cross-sectional study of 592 secondary data of COVID-19 patients undergoing treatment in the ICU and hospitalizations who carried out ferritin examinations from January to December 2021 at Persahabatan Hospital. Research data were analyzed using the Mann-Whitney Test.Results: The mean value of ferritin levels in ICU patients was 2,406.7 ng/mL and inpatients was 1,249.6 ng/mL. The results of the Mann-Whitney Test obtained a p value of 0.000 <0.05 so that Ho was rejected, which means that there was a significant difference between ferritin levels in patients treated in the ICU and hospitalized at Persahabatan Hospital.Conclusion: There is a significant difference between ferritin levels in COVID-19 patients treated in the ICU and hospitalized in Persahabatan Hospital. Examination of ferritin levels can indicate severe inflammation in COVID-19 patients.